Princípios da construção enxuta no processo de planejamento de uma construtora de grande porte de Natal (RN) - Borges, Thyago de Melo Duarte (2016)
The civil construction represents one of the most important sectors for the economic growth of a country. To make this industry grow it is necessary to implement an effective planning in activities. This is one of the most important concepts brought by the Lean Construction philosophy. The main goal of this article consists in investigating how the 11 principles of the lean construction influenced the schedule of a construction field. As a methodology, it was used the case study of a big enterprise located in Natal (RN). During the execution of the method, documents were analysed , it was also described the factors that caused the delays at the enterprises’ field , the actions were listed by the company, which had the purpose to solve the main causes of delays, verifying if they were linked to the lean construction principles. This research it is relevant because the principles of the lean construction uphold the reduction of processes that are useless, diminishing wastes as well as costs in construction. Among the main results, the high frequency of planning errors stands out, mainly the programming deviations and not the task programming, as well as the execution errors, low productivity and activities executed by the workers. Amongst the 11 principles of lean construction, only five were related with the 12 actions analysed by the author. From the 12 actions, four were completely cohesive to one or more from these five principles. Some improvement proposals were also highlighted and established by the research